Bridging digital innovation and cultural heritage: Integrating technology to foster Dompu local culture in early childhood education - Ihlas Ihlas; Umar Umar; Evi Selva Nirwana (Journal of Educational Management and Instruction (JEMIN), 2026)
The rapid expansion of digital technology has transformed children's learning experiences while simultaneously raising concerns about the preservation of local cultural heritage. In early childhood education, integrating digital technology with culturally relevant learning offers opportunities to strengthen children's cultural identity and sense of belonging. This study aimed to explore how digital technology is utilized to introduce Dompu local culture in early childhood education settings and to examine the factors influencing its implementation. Employing a qualitative approach with an ethnographic orientation, the research was conducted in four early childhood education institutions in Dompu Regency, Indonesia. Data were collected through classroom observations, semi-structured interviews with school leaders, teachers, and parents, as well as document analysis. The findings reveal that digital technology serves as an effective medium for introducing various aspects of Dompu culture, including rimpu, traditional welcoming dances, local folklore, traditional houses, and cultural food practices. Interactive digital content enhanced children's interest, participation, and understanding of cultural symbols and values. The study further found that teacher mediation and parental involvement were critical factors shaping the effectiveness of digital cultural learning. The findings highlight the importance of culturally responsive digital pedagogy and suggest that technology can function as a bridge between young learners and local cultural heritage when supported by meaningful educational practices and collaborative home–school partnerships.